GWANCANA (Women's Movement to Prevent Anemia) in Improving Adolescent Health Independence at PAB 8 Middle School Sampali Medan: GWANCANA (Gerakan Wanita Cegah Anemia) Dalam Peningkatan Kemandirian Kesehatan Remaja di SMP PAB 8 Sampali Medan - Warnelis Sinaga, Elvalini; Gultom, Risatantry; Samgryce Siagian, Hartika; Christy, Johanna; Veronika, Ida; Priscillia, Prilly (Universitas Haji Sumatera Utara, 2025)
One of the nutritional problems faced by adolescents is anemia. Anemia is defined as a decrease in blood hemoglobin (Hb) levels below normal values for age and gender. Common Hb values are <13.5 g/dL in adult men and <11.5 g/dL in adult women. Several factors that influence adolescents to experience anemia are unhealthy eating patterns, limited sources of knowledge and skills, lack of commitment from the school, and lack of student understanding of the dangers of anemia. The implementation of the GWANCANA program is to increase the independence of adolescent girls in preventing anemia by utilizing and reactivating the School Health Unit by forming a women's movement to prevent anemia. The target of community service counseling is adolescent girls at SMP PAB 8 SAMPALI Junior High School, Jl. Pasar Hitam No.69, Percut Sei Tuan District, Deli Serdang Regency, Sumatra Province, this aims to increase the independence of adolescent girls in preventing anemia by utilizing and reactivating the School Health Unit by forming a women's movement to prevent anemia (GWANCANA). Respondents from the counseling activities were all 124 young women. The method used was to measure knowledge first to see the increase in knowledge before and after the counseling was carried out using several media such as: questionnaires, posters, ppt and leaflets to attract the attention of female students of SMP PAB 8 SAMPALI. The knowledge of young women where the average previous knowledge value was 45.2 and after being given counseling increased to 89.1 This women's movement to prevent anemia plays a very important role in increasing the independence of young women in improving their health.